Anticipation of magnetic and electrical stimuli does not impair maximal voluntary force production. (15th August 2016) - Peyrard, Arthur; Sawh, Paul; Fan, Selina; Temesi, John; Millet, Guillaume Y.
Highlights: Knowing that evoked stimulation will be delivered does not impair maximal force. Discomfort was greatest for electrical muscle stimulation. Discomfort was least for transcranial magnetic stimulation. Nerve and cortical interpolated twitch technique is valid for both men and women. Abstract: Introduction: Knowing electro-myostimulation (EMS) will be delivered during a maximal voluntary contraction (MVC) has been demonstrated to limit maximal force production in the knee extensors. Many recent studies instead deliver peripheral nerve stimulation (PNS) or transcranial magnetic stimulation (TMS) during MVCs to assess neuromuscular function. This study investigated the effects of EMS, PNS and TMS on maximal voluntary force production and muscle activation in the knee extensors. Methods: Nineteen healthy participants performed MVCs under 8 randomized conditions: no stimulation, TMS at 40% of maximal stimulator output, TMS at 70% of maximal stimulator output, single-pulse PNS, paired (100-Hz)-pulse PNS, single-pulse EMS and two conditions where subjects expected TMS at 70% of maximal stimulator output or paired-pulse PNS yet no stimulus was delivered. Knee extensor force, discomfort associated with the stimulus and vastus lateralis, rectus femoris and biceps femoris electromyography (EMG) were recorded. Results: There were no differences between MVC forces and maximal agonist and antagonist muscle activity between conditions. Discomfort was greatest for EMS and least for TMS. Conclusion: This study demonstrates that in familiarized subjects, knowing a stimulus (EMS, PNS or TMS) will occur does not impair maximal force or EMG produced despite differences in discomfort associated with the stimulus modalities. These techniques can be used to investigate central drive and peripheral function, at least for intensities comparable to those employed in the present study.